2022
DOI: 10.3390/ani12020142
|View full text |Cite
|
Sign up to set email alerts
|

Improving Trapping Efficiency for Control of American Mink (Neovison vison) in Patagonia

Abstract: Two main challenges when controlling alien American mink (Neovison vison) in Patagonia are to maximize campaign efficacy and cost-effectiveness and to avoid trapping native species. We designed and tested new variants of collapsible wire box traps, compared the efficacy of a food-based bait and a scent lure and compared catch rates in different seasons of the year. We used the data to model the efficiency rate of the trapping and to determine the trapping effort required to remove 70–90% of the estimated discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…Indeed, the efficiency values of these trials are among the highest and consequently, those improvements might be applied in future large-scale management programs on the continent. The conclusions of Medina-Vogel et al (2022) agree with previous studies on trap spacing effect in mustelids (King 1980;Melero et al 2008) that showed the best capture rates, especially the concurrent capture of females and males were with traps set at 200-meter intervals Some other remarkable conclusions have been short trapping periods in each site; and the design of a smaller, cheaper and species-specific trap variant GMV-13. These studies also confirm that the use of scent gland lures increases mustelid trap efficiency (Clapperton et al 2017;Roy et al 2006) and agree with Zuberogoitia et al (2010) that trapping efforts should be focused in certain seasons of the year (Medina-Vogel et al 2022).…”
Section: )supporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, the efficiency values of these trials are among the highest and consequently, those improvements might be applied in future large-scale management programs on the continent. The conclusions of Medina-Vogel et al (2022) agree with previous studies on trap spacing effect in mustelids (King 1980;Melero et al 2008) that showed the best capture rates, especially the concurrent capture of females and males were with traps set at 200-meter intervals Some other remarkable conclusions have been short trapping periods in each site; and the design of a smaller, cheaper and species-specific trap variant GMV-13. These studies also confirm that the use of scent gland lures increases mustelid trap efficiency (Clapperton et al 2017;Roy et al 2006) and agree with Zuberogoitia et al (2010) that trapping efforts should be focused in certain seasons of the year (Medina-Vogel et al 2022).…”
Section: )supporting
confidence: 87%
“…Many factors that increase efficiency have been highlighted in this review like the use of attractants, mainly olfactory ones, short trapping periods or increasing lineal coverage. In addition, there are some others that have been proposed previously like the new traps variant design and to concentrate culling only during certain seasons (Medina-Vogel et al 2022), the use of spatial and genetic knowledge about local mink populations (Adams et al 2014;Fraser et al 2013) or to employ sniffers dogs and techniques to flush out (as mentioned on page 44) resident mink in some stages or areas (Moore et al 2003). The selection of the most efficient techniques and protocols not only helps to achieve management proposals efficiently, but also reduces the associated costs, making control sustainable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these odours were effective in attracting ferrets and stoats [50][51][52], synthetic lures made from the active ingredients were less attractive to stoats than to ferrets [53], and trials were discontinued. However, anal gland odours have been used successfully as trap lures to control another mustelid pest, the American mink (Neovison vison Schreber) [54][55][56]. Commercial lures containing unspecified polecat (Mustela putorius) and marten (M. foina) glandular secretions also increased the probability of detecting mustelids at camera-trap monitoring sites compared with no attractant [57].…”
Section: Introductionmentioning
confidence: 99%